Equilibrium exchange rates in transition countries: Evidence from dynamic heterogenous panel models - Byung-Yeon Kim; Iikka Korhonen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2002)
We use a dynamic heterogeneous panel model to estimate real equilibrium exchange rates for advanced transition countries.Our method is based on out-of-sample estimations from middle-income and high-income countries, and we use a pooled mean group estimator.We find that exchange rates have converged in recent years in five transition countries (Czech Republic, Hungary, Poland, Slovakia, and Slovenia) with real equilibrium exchange rates expressed in the US dollars.However, we also find that the currencies of the transition countries studied are substantially overvalued if real effective exchange rates are used.
URN:NBN:fi:bof-201408072022
Keywords: C33; F31; P27; 330; exchange rates; transition economies; dynamic heterogeneous panel estimations